Gambaran Budaya Patriarki dalam Film Ngeri-Ngeri Sedap - Felix, Felix; Pandrianto, Nigar (Koneksi, 2023)
Watching movies is one of the most popular forms of entertainment for the public. The film, as a mass media, is often used to comment, criticize, give messages, to instill values ​​in society. The patriarchal cultural system is a system that is still widely embraced by several cultures in Indonesia and even the whole world. Therefore, patriarchy is often used as an issue raised in a film. The Missing Home film, which received a nomination for the best international feature film category at the 2023 Academy Awards, is one of the films that raise the issue of Patriarchy. This film tells about a conflict that arises between a father with his wife and their four children due to the patriarchal culture they live in. This study aims to determine the depiction of patriarchal culture in the Missing Home film. This study uses a descriptive qualitative approach, with John Fiske's semiotic analysis. Semiotic analysis is done on the Missing Home film. Data collection was carried out by documenting several scenes in the film and conducting interviews with a film producer as a research triangulator. This study found that there is a depiction of patriarchal culture which is symbolized by the elements in the Missing Home film. This depiction shows that the male characters in the film are more dominant, superior and powerful, while the female characters tend to be submissive and yielding. The ideology and conflict in the film NNS are also a picture of the social life of the Indonesian people. Conflict resolution in this film can become a new value ​​for society. Menonton film merupakan salah satu hiburan yang paling digemari oleh masyarakat. Film sebagai media massa sering digunakan untuk mengomentari, mengkritik, memberi pesan, hingga menanamkan nilai-nilai pada masyarakat. Sistem budaya patriarki merupakan sistem yang masih banyak dianut oleh beberapa budaya di Indonesia bahkan seluruh dunia. Oleh karena itu, patriarki sering menjadi isu yang diangkat dalam sebuah film. Film Ngeri-Ngeri Sedap yang mendapat nominasi di kategori film fitur internasional terbaik di Academy Awards 2023 adalah salah satu film yang mengangkat isu patriarki. Film ini menceritakan tentang sebuah konflik yang timbul antara sosok ayah dengan ibu serta keempat anaknya akibat budaya patriarki yang dijalaninya. Penelitian ini bertujuan untuk mengetahui penggambaran budaya patriarki yang ada dalam film Ngeri-Ngeri Sedap. Penelitian ini menggunakan pendekatan kualitatif deskriptif, dengan analisis semiotika John Fiske. Analisis semiotika dilakukan pada film Ngeri-Ngeri Sedap. Pengumpulan data dilakukan dengan mendokumentasi beberapa scene dalam film serta dilakukan wawancara dengan seorang produser film sebagai triangulator penelitian. Penelitian ini menemukan bahwa ada sebuah penggambaran budaya patriarki yang tersimbol lewat elemen-elemen pada film NNS. Penggambaran tersebut menunjukan tokoh laki-laki dalam film yang lebih dominan, superior, dan berkuasa, sedangkan tokoh perempuan yang cenderung tunduk dan mengalah. Ideologi dan konflik yang ada pada film NNS juga merupakan gambaran kehidupan sosial masyarakat Indonesia. Penyelesaian konflik dalam film ini dapat menjadi nilai-nilai baru bagi masyarakat.